2018
DOI: 10.1016/j.preghy.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Arm and finger measurements in the third trimester: Implications for blood pressure measurement

Abstract: To obtain arm and finger measurements of women ≥32 weeks gestation to determine: the requirement for different arm cuff sizes; the suitability of available finger cuffs in this population; the best predictor of arm conicity; the frequency of cuff placement on the forearm or leg. Study Design Prospective observational pilot study. Main outcome measures Right and left mid-arm circumference (MAC) and to compare these to the recommended cuff sizes; right and left finger circumference; right and left arm conicity; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 22 publications
9
26
0
Order By: Relevance
“…In addition to MAC, BMI and weight were also correlated with conicity index, and of the three variables, BMI was found to correlate the best with arm conicity. These results are similar to that of Eley et al, who also reported that BMI correlated best with arm conicity, accounting for 26% of the variation in conicity index [3]. Furthermore, our nding that BMI, weight, and MAC were collinear was also reported by Eley et al [3].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition to MAC, BMI and weight were also correlated with conicity index, and of the three variables, BMI was found to correlate the best with arm conicity. These results are similar to that of Eley et al, who also reported that BMI correlated best with arm conicity, accounting for 26% of the variation in conicity index [3]. Furthermore, our nding that BMI, weight, and MAC were collinear was also reported by Eley et al [3].…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to that of Eley et al, who also reported that BMI correlated best with arm conicity, accounting for 26% of the variation in conicity index [3]. Furthermore, our nding that BMI, weight, and MAC were collinear was also reported by Eley et al [3]. This may be explained by the association between increasing BMI and higher MAC in both pregnant [3,17,18] and non-pregnant populations [19], and is likely due to an increase in arm fat mass as measured using bioelectrical impedance analysis [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results highlight the fact that currently available devices using alternate sites, such as the finger, do not adequately cater to all patients who have obesity either. The largest finger cuff supplied by ClearSight was not large enough for all our patients, and this failure also was demonstrated in a pregnant population . While the sizes of the finger cuffs supplied with the CNAP device are ample, the device requires the use of a NIBP arm cuff for calibration.…”
Section: Discussionmentioning
confidence: 88%